Millets: Need of the Hour – An Overview - Katole, Ashwini; Jha, Anupriya; Giri, Purushottam (Indian Journal of Community Health, 2025)
This comprehensive article investigates millet’s role in supporting sustainable agriculture and mitigating global health issues, especially malnutrition. A varied family of small-seeded grains, millets are very essential source of nutrients and plays very crucial role in a gluten-free, high-nutrient substitute for traditional cereals. The article examines India's initiatives to grow and promote millets, highlighting the crop's critical role in preventing malnutrition, addressing lifestyle-related health problems, and fostering food security. India is a significant millet producer. The United Nations proclamation of the International Year of Millets highlights 2023, the significance of millets recognised worldwide. India's state-specific programmes and legislative actions show a concerted attempt to promote millet as a staple grain in line with global health and development objectives.